Measurements of a 5:1 blood pump model - Zheng, Yanyu (2019)
This report presents the measurements of the flow in the clearance gap of a 5:1 scaled up model of Kyoto University Magnetically Suspended Centrifugal Blood Pump, which uses magnetically suspended impeller to eliminate any physical blood contact with the bearing and seal, hence lower heat generation effect and contamination of blood. However, hemolysis and thrombus formation in the 0.2mm clearance gap in between the pump casing and the impeller surface of the prototype pump is a major problem. The scaled-up model was built five times larger since there is no measuring tool can measure the flow with only 0.2mm width. Hot wire anemometry was used to measure the tangential and radial velocity at 3 different protrusion depths (0.25mm, 0.5mm, 0.75mm) between the casing and impeller. The readings were measured at 7 different radial position and 72 angular position with a 5° intervals, from 0° to 360°. A total of 504 readings (7 radial x 72 angular) were taken at each axial plane. The results of the measurements were presented by the plots at the chapter of results and discussion. The results show that there was a good washout in the clearance gap. Hence, reducing the chance of thrombus formation and blood clot aggregation.